Human Papilloma Virus genotypes in Type III cervical intraepithelial neoplasia. Cuenca-Ecuador, 2013-2017 - Patricio Santiago Tigre Sinchi; Zoila Katherine Salazar Torres; Lizette Espinosa Martin; Karla Alexandra Aspiazu Hinostroza; Hermel Medardo Espinosa; Freddy Rosendo Cárdena Heredia (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2019)
Cervical cancer is one of the most common cancers in female population worldwide in underdeveloped countries, and in Ecuador it stands out in second place. This research focuses on HPV-genotype description in type III-intraepithelial neoplasms. The study type was analytical, retrospective and cross-sectional. The sample was 195 patients with NIC III diagnosis, from 20 to 60 years old, who were in the data system of "Sociedad de Lucha Contra el Cancer" Cuenca-Ecuador, 2013-2017 term. It was established that HPV-16 genotype was in 32.9% (n 51) of all cases; factors like sociodemographic variables, tobacco use, infection, hormonal contraceptives use, more than one sexual partner, age of start of active sex life equal or less than 20 years old, didn´t show a relationship with HPV infection; on the other hand, IUD use and HPV-16 infection had a statically significant relationship (OR 2,75; CI 95% 1,21-6,26; p 0,01). HPV genotype HPV-16 was the most common, and IUD use was a risk factor to get HPV infection